Investigations into influences of wind field resolution on simulating surface currents for Galway Bay. (October 2017) - Ren, Lei; Nagle, Diarmuid; Nash, Stephen; Hartnett, Michael
Abstract: Inaccurate wind data can lead to inaccuracies in the surface currents computed by three-dimensional hydrodynamic models. In the present research, a wind forecast model is coupled with a 3D hydrodynamic model to investigate the effect of surface wind data resolution on model accuracy. High resolution and low resolution wind fields are specified to the model and the computed surface currents are compared with measurements obtained from the High-Frequency (HF) radar observation system and Acoustic Doppler Current Profile. Modelled surface currents show good correlation with observations and the resolution of the surface wind data is shown to be important for model accuracy.